Features of Administrative Liability of Minors (Law and Safety, 2019)
The need to consider the peculiarities of juvenile administrative liability is grounded by the increase in the number of offenses committed by them.Scientific approaches to the definition of the concepts of “administrative liability” and “administrative liability of minors” have been analyzed. In order to distinguish administrative liability from other types of legal liability, the author has studied the features of direct administrative liability.It has been established that juvenile administrative liability has features that are related to the age of a person who is brought to liability and are associated with the specific protection of the minor’s interests. The peculiarities of juvenile administrative liability have been distinguished and systematized; and it has been offered to divide them into material and procedural ones. Material peculiarities include: the age, when the specified type of liability comes due; predominantly educational nature of administrative liability; the fact that the purpose of administrative liability of a minor causes a lesser amount and degree of deprivation or restriction of the rights and freedoms compared to persons who are over 18 years old; the fact that administrative liability, in some cases, arises on general basis. The procedural peculiarities of juvenile administrative liability are related to its judicial application, the possibility of applying administrative and coercive measures to the parents of a minor, the participation of legal representatives and representatives in the representation of their interests, the obligation to notify the parents or persons who replace them, about minor’s detention, and with impossibility to apply administrative penalties as a substitute for criminal liability.The author has formulated his own definition of the concept of administrative liability of minors. It has been emphasized that the age peculiarities of juveniles should be taken into account while bringing a minor to administrative liability, and the nature of the committed administrative offense should be commensurate with the enforcement action.
Keywords: administrative liability; administrative liability of minors; administrative offenses; enforcement action; minors